Howe’s dental cast analysis of students at the University of Sumatera Utara - Hilda Fitria Lubis; Tiopan Beltsazar Sinurat (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Cast analysis is the measurement of the upper and lower arch in a 3-dimensional occlusal relationship. Howe’s Analysis can be used to observe total tooth material, arch length, and basal arch width. Howe’s Analysis was conducted to analyse abnormalities of both teeth and the jaw to help diagnose and plan dental care. Purpose: To analyse the difference in total tooth material, arch length, basal arch width, and Howe’s Index between male and female undergraduate students from the University of Sumatera Utara who are of Proto-Malay origin. Methods: Ninety-six samples comprised of 48 male and 48 female students were recruited through the purposive sampling method. All samples were undergraduate students at the University of Sumatera Utara and of Proto-Malay origin, aged between 18 to 26, and have met the exclusion and inclusion criteria. We measured the variables using a digital caliper to measure basal arch width and arch length and Moorrees’ method to measure total tooth material. Data were analysed statistically using an independent t-test to compare means between groups (p<0.05). Results: The male samples’ average value of total tooth material 98.49 mm±3.79, arch length 45.55 mm±2.28, basal arch width 41.07 mm±2.83, and Howe’s Index were 41.71 %±2.63, respectively. The female samples had a lower value compared to the male samples, 94.51 mm, 43.27 mm, 36.89 mm, and 39.05 % respectively. There was a significant difference in the total tooth material, arch length, basal arch width, and Howe’s Index between male and female undergraduate students from the University of Sumatera Utara of Proto-Malay origin (p=0.001; p<0.05). Conclusion: The average measurement of total tooth material, arch length, basal arch width, and Howe’s Index was higher in male than female undergraduate students from the University of Sumatera Utara of Proto-Malay origin.